Determination of Gemifloxacin in human plasma by high performance liquid chromatography using Ultra Violet detector and its application to a bioequivalence study - Syed Husain Hashemi Mousavi (Universidade de São Paulo, 2019)
A liquid chromatography method was developed and validated for the determination of gemifloxacin in human plasma using chloramphenicol as internal standard to achieve lower quantification limit. Acetonitrile was used to precipitated and extracted analyte and internal standard from plasma by Protein Precipitation. Analysis was performed isocratically on C18 column using 25% acetonitrile and 75% 0.02 M phosphate buffer as mobile phase. The method was demonstrated to be linear from 0.003 µg/mL to 5 µg/mL with the lower limit of quantitation of 0.003 µg/mL. The method was successfully applied for the bioequivalence study of gemifloxacin after a single oral administration of 320 mg gemifloxacin mesylate tablets to 12 healthy volunteers.